Évolution des rapports entre les États débiteurs de l’Amérique latine et les créanciers occidentaux - Jedlicki, Claudio (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
This article is about the problem of the debt incurred by countries of Latin America, preference being given to the notion of net transfer of currency as being the main element which can explain relations between debtors and creditors. It shows that the recent evolution in the attitude of the debtor states, as has been apparent since the meeting at Quito, in January 1984, up to that at Mar del Plata in September 1984, is accounted for by the inversion of the flow of the net transfer of money. Latin America today has become a net exporter of currency.Similarly, the future evolution between the pursuance of the monetary adjustment and the cessation of payment will be determined, in a large measure, by the scope and the meaning lying behind the net transfer of borrowed money. The economical, social and political consequences deriving from the actual reimbursement of the debt are such that they may promote the advent of regimes which will be compelled to implement deep structural reforms. Whether this comes about or not will depend a lot on the creditors.